Those Amazing Animals (African Knowledges and the History Publication since the 1970s)
Talk show segment on different animal related topics: Giant clam poachers on Australias coasts; wildlife protection and foothold traps; drug sniffing dogs; and dog breeding.
Keywords: Education; Entertainment